Polycystic ovary syndrome: Criteria, phenotypes, race and ethnicity - Tsuyoshi Baba (Reproductive Medicine and Biology)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex endocrinopathy, which leads to ovulation dysfunction and infertility, as well as metabolic and mental disorders. Women with PCOS exhibit several characteristic symptoms, with marked heterogeneity across different races and ethnicities. Methods In this review, the author outlines the phenotypic disparities of PCOS among various racial and ethnic populations. First, the prevalence of major symptoms in different racial and ethnic groups with PCOS is summarized. Next, the effects of four phenotypes, derived from the Rotterdam criteria for PCOS, on metabolic and reproductive features are recapitulated. Main Findings A growing body of evidence suggests that East Asian populations exhibit less hirsutism and adiposity compared with other groups. However, hirsutism is more prevalent in South Asian, Middle Eastern, and Hispanic populations. Hispanic and African American populations have more frequent obesity and insulin resistance. With regard to the association between mental disorders and racial and ethnic differences, limited studies exist; therefore, no conclusions can be drawn. Conclusion Race and ethnicity‐specific factors related to PCOS must be considered in clinical practice. The diagnostic criteria of PCOS should be specific to race and ethnicity to avoid missing treatment opportunities.